Pengaruh Gaya Kepemimpinan Dan Kinerja Aparatur Pemerintah Desa Terhadap Kualitas Pelayanan Masyarakat Desa Ngumpul Kecamatan Bagor Kabupaten Nganjuk - Juarinik Juarinik; Suparni Suparni (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2018)
This research aims to find out if the leadership style and performance the influential Government Apparatus in a partial and simultaneous to the quality of Ngumpul Village and subdistrict community service Bagor Nganjuk Regency.In this study only reveal the influence of leadership styles and the village government performance against quality community service Village Ngumpul, district Bagor, Nganjuk Regency, then research that identified the leadership style that is intended a leader to provide direction to subordinates, poorly understood by a leader that governs employee is a difficult and complex case, community/public trust towards the Government or bureaucratic performance decline since complaints and complaints from the public against the Ministry.This proves that the quality of public services is an important component to look for in the public service and the need for unification of directions and view as a guideline or reference in carrying out the task of good managerial or operational in an effort to increase the capabilities of employees aiming to improve the performance impact on the improvement of community service. This type of research using quantitative methods with the approach of the survey. The population used in this research is the ngumpul village community composed of 8 hamlets, samples used as many as 94 responde a later analysis using multiple linear regression analysis and hypothesis testing in partial test with t and simultaneous hypothesis testing with test F. The results in this study concluded that the leadership style and the performance of the apparatus is partially positive effect to the quality of community service in the village of Ngumpul, district Bagor, Nganjuk attested to the value t calculate larger from the t table and its significance less than 0.05.2) Style of leadership and influential apparatus simultaneous performance of the quality community service in the village of Ngumpul, district Bagor, Nganjuk attested to the value of F is greater than the count F table and its significance less than 0.05.